Description of the second instar larva of Thermothrips mohelensis Pelikán (Thysanoptera: Thripidae) - Ulitzka, Manfred R.; Evdokarova, Taisia G.; Moritz, Gerald (Zootaxa, 2020)
Thermothrips mohelensis Pelikán is an extremely rare thrips found in dry steppe grassland ecosystems (Pelikán 1949, 1995; Ulitzka 2019a). It has been reported from only a few locations and almost always in very low abundance: one female each has been collected in Germany (Ulitzka 2019a), Slovenia (Kucharczyk 2008) and Turkey (Tunç 1992), two females are known from Iran (Mirab-balou & Chen 2013), three from Poland (Zawirska 1988; Kucharczyk 2007) and six from Western Russia (Schliephake 1977). Larger series including males and larvae are known only from Czechoslovakia (Pelikán 1949, 1995) and from Yakutia, East Siberia where—besides other specimens—the larvae discussed below have been collected (see Evdokarova & Kucharczyk 2020). The fragmented and selective occurrence of this species in steppe habitats has been interpreted to represent scattered relict populations that may have remained from a more extensive distribution far back, possibly in the wide dry grasslands of the Late Pleistocene (Ulitzka 2019a). Similar to other specialist species of those barren habitats T. mohelensis is severely threatened by the general decline of these fragile ecosystems due to natural succession or anthropogenic impact (Kucharczyk 2008; Kucharczyk & Kucharcyk 2008; Ulitzka 2019a). T. mohelensis is a thermophilous (zur Strassen 2003) and highly xerophilous species. This thrips was erroneously considered an hydrophilous wetland thrips (Bhatti 1998) due to a mistranslation (see Ulitzka 2019a). T. mohelensis lives and breeds monophagously in flowers of Galium (Rubiaceae), particularly G. verum but also G. mollugo (Pelikán 1949, 1995; Schliephake 1972; Tunç 1992).